2014
DOI: 10.1159/000363075
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of MRI for the Assessment of Mesorectal Fascia Involvement in Patients with Rectal Cancer: A Systematic Review and Meta-Analysis

Abstract: Aims: Defining the most appropriate definition of mesorectal fascia involvement (MRF+) by reviewing literature and using new inclusion criteria to re-evaluate the effectiveness of MRI in the assessment of MRF+ for rectal cancer. Methods: PubMed, Medline, Embase, and the Cochrane Library databases were electronically searched from 1999 to 2012. The bivariate random effects model was used to estimate the pooled outcomes of each subgroup. The definition of MRF+ in MRI and the influence of neoadjuvant chemoradioth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 56 publications
(85 reference statements)
0
16
0
Order By: Relevance
“…Several studies specifically investigated the possibility of defining a line between 1 and 5 mm as the threshold to diagnose CRM involvement on MRI. According to a recent meta-analysis (42), of three different threshold values of 1, 2, and 5 mm for the shortest tumor distance from the mesorectal fascia on MRI, the highest overall accuracy for diagnosing CRM involvement, demonstrating 76% pooled sensitivity, 88% pooled specificity, and diagnostic odd ratio of 22.4, was observed for a distance of 1 mm. Another study analyzed the risk of local recurrence according to the shortest tumor distance from the mesorectal fascia on MRI and showed that, relative to the distance > 5 mm, the risk of local recurrence was not significantly different in 1–2 mm and 2–5 mm groups, but was significantly higher in ≤ 1 mm group (hazard ratio of 3.72) (39).…”
Section: Elaboration On the Reporting Items Formats And Their Clinimentioning
confidence: 99%
“…Several studies specifically investigated the possibility of defining a line between 1 and 5 mm as the threshold to diagnose CRM involvement on MRI. According to a recent meta-analysis (42), of three different threshold values of 1, 2, and 5 mm for the shortest tumor distance from the mesorectal fascia on MRI, the highest overall accuracy for diagnosing CRM involvement, demonstrating 76% pooled sensitivity, 88% pooled specificity, and diagnostic odd ratio of 22.4, was observed for a distance of 1 mm. Another study analyzed the risk of local recurrence according to the shortest tumor distance from the mesorectal fascia on MRI and showed that, relative to the distance > 5 mm, the risk of local recurrence was not significantly different in 1–2 mm and 2–5 mm groups, but was significantly higher in ≤ 1 mm group (hazard ratio of 3.72) (39).…”
Section: Elaboration On the Reporting Items Formats And Their Clinimentioning
confidence: 99%
“…When CRM involvement was defined as a tumor within 1 mm of the mesorectal fascia, MRI had a specificity and sensitivity of 76 and 88%, respectively. 44 CRM involvement is a poor prognostic factor in rectal cancer. 45,46 Long-term follow-up of the MERCURY study showed that 5-year overall survival was 62.2% in the CRMnegative group compared with 42.2% in the CRM-positive group and was the only significant prognostic risk factor for overall survival (OS), DFS, and local recurrence (LR) on multivariate analysis.…”
Section: Circumferential Resection Marginmentioning
confidence: 97%
“…28 In a meta-analysis of thresholds of 1, 2, and 5 mm for the shortest tumour distance from mesorectal fascia on MRI, using ≤1 mm to define CRM involvement had the highest overall accuracy, with 76% pooled sensitivity, 88% pooled specificity, and diagnostic odds ratio of 22.4. 31 The European Society of Gastrointestinal and Abdominal Radiology and the Korean Society of Abdominal Radiology also recommend a cut-off of ≤1 mm to define tumour-involved CRM on MRI, 5,32 and a cut-off of ≤2 mm to define a threatened CRM on MRI. 5 Apart from direct extension from the primary tumour, other high-risk features in the mesorectum (such as extramural venous invasion, vascular / tumour deposits, and less likely metastatic nodes) can also cause tumourinvolved CRM (Figure 8).…”
Section: Circumferential Resection Marginmentioning
confidence: 99%